N-(2-ethylphenyl)phthalimide - Ariffin, Azhar; Ng, S.W.; Fan, Y.M.; Zakaria, N. (International Union of Crystallography, 2008)
In the title compound, C(16)H(13)NO(2), the phthalimide and benzene ring systems form a dihedral angle of 77.2 (1)degrees.